Dielectric relaxation in pure and irradiated TGSP crystals - Arunmozhi, G. (2000)
Low frequency dielectric measurements in triglycine sulpho-phosphate (TGSP) and gamma-irradiated TGSP crystals were carried out around the ferroelectric to paraelectric phase transition. The dispersion found in the ferroelectric phase cannot be explained only by a Debye equation with a single relaxation time. The ratio of the Curie constants in the para- and ferroelectric phase (C-p/C-f) for the irradiated TGSP samples show that the crystal is partially clamped. The deviations from the typical single relaxation behaviour are more pronounced in irradiated samples clearly indicating the contribution of defects in addition to the impurities to the dynamics of the system